2015
DOI: 10.1016/j.snb.2015.06.088
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sensitive detection of norovirus antibodies in human serum with a biolayer interferometry biosensor

Abstract: a b s t r a c tHere, we describe the use of a biolayer interferometry biosensor for the fast and sensitive detection of virus-specific antibodies from human serum samples. Norovirus-like particles and norovirus P-particles were used to functionalise the biosensor tip. The detection of antibodies directly from serum samples was challenging, but the addition of a metal chelator (DAB) combined with an anti-human horseradish peroxidase-tagged antibody enabled enhanced detection of virus-specific antibodies in seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Aside from SERS and SPR, a number of other optical biosensor methods, including biolayer interferometry, fluorescence, bioluminescence and colorimetric based biosensors have also been shown to successfully detect NoV. For example, a label-and fluidic-free detection system based on a biolayer interferometry (BLI) biosensor has been proven to be able to detect NoV antibodies from human serum samples [145]. The scheme is depicted in Figure 3.…”
Section: Other Optical Biosensor Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Aside from SERS and SPR, a number of other optical biosensor methods, including biolayer interferometry, fluorescence, bioluminescence and colorimetric based biosensors have also been shown to successfully detect NoV. For example, a label-and fluidic-free detection system based on a biolayer interferometry (BLI) biosensor has been proven to be able to detect NoV antibodies from human serum samples [145]. The scheme is depicted in Figure 3.…”
Section: Other Optical Biosensor Methodsmentioning
confidence: 99%
“…The scheme is depicted in Figure 3. This assay is considered rapid (10~20 min if the sensor was pre-functionalized) and could detect NoV antibodies in serum dilutions up to 1:100,000 [145]. Similarly, Auer et al [144] used a Co (III)-NTA functionalized BLI sensor immobilized with His-tagged VLPs for the detection of NoV antibodies from human serum.…”
Section: Other Optical Biosensor Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Selvarajah et al immobilized the chikungunya virus VLPs onto amine reactive biosensors to screen the response of two human IgG Fabs, C9 and E8. Auer et al used histidine‐tagged Noroviruses (Nov) VLPs on the Ni‐NTA sensors to directly detect its antibodies in human serum. Carvalho et al demonstrated the ability of BLI to detect and quantify label‐free influenza VLPs and model mucins.…”
Section: Introductionmentioning
confidence: 99%